Reception of adolescents with suicidal ideation and attempts (Research, Society and Development, 2023)
This article is an integrative review of the literature that aims to investigate the main strategies for preventing suicide among young people. The search was conducted in electronic databases and included studies that addressed suicide prevention strategies in different youth populations, including LGBTQ+, Indigenous, and university students. The analysis of the results showed that the main strategies include promoting mental health, access to diverse and sensitive mental health services, creating safe and inclusive environments, collaboration between health and education systems, involving families and communities, taking a multidisciplinary approach, and promoting Indigenous culture and traditions. The final considerations highlight the importance of personalized approaches, adapted to the specific needs of each group, and the need for further studies to improve suicide prevention strategies among young people. The three keywords are: suicide, prevention, youth.